Digital for the strengthening of writing skills in teachers of basic secondary - Rosa-Coronado, María (2023)
The use and interpretation, comprehension and production of texts through different networks and virtual platforms that can be replicated in their educational praxis through the construction of flexible learning environments relevant to current educational needs. The research was raised from the holistic understanding, following the parameters of the Holopráxico method and corresponds to a projective type investigation since the final objective of this research allows to propose solutions to a certain situation, starting from a process of inquiry. The analysis technique used was descriptive and frequency statistics; to determine the influence between both events, the Ordinal Logistic Regression test was applied, whose value of theoretical significance is 0.000 < 0.05, which indicates that there is a significant influence of the use of ICT in strengthening the writing skills of teachers of secondary and secondary school. The selected population was 111 teachers of Secondary and Secondary Basic Education of the thirty-six educational institutions of the district of Turbo, Colombia of which nine belong to the urban sector and the remaining twenty-seven to the rural sector